Contrast-enhanced ultrasound findings of ovarian Sertoli-Leydig cell tumor: a case report with ultrasonographic–pathological insights - Siting Lin; Man Zhang; Manli Wu; Xinling Zhang (BMC Women's Health)
Abstract Background Ovarian Sertoli-Leydig Cell Tumors (SLCTs) are exceedingly rare sex cord-stromal tumors with non-specific clinical features and limited diagnostic imaging. We evaluated the ultrasonographic-pathological correlation of ovarian SLCT and explored the clinical value of contrast-enhanced ultrasound (CEUS) through a case analysis of a 62-year-old woman with a SLCT. Case presentation A 62-year-old postmenopausal woman presented with abdominal distension. Serum testosterone was elevated (4.43 nmol/L; normal range 0.45-1.26nmol/L). Ultrasound revealed a large multilocular cystic lesion with solid components in the pelvic-abdominal region, marked by abundant blood flow within the septa and solid areas, along with low-resistance arterial flow in the solid component of the tumor. CEUS demonstrated rapid and heterogeneous high enhancement in the tumor’s cystic wall, septa, and solid components during the wash-in phase. Additionally, there was early washout compared to the myometrial layer. Total hysterectomy with bilateral salpingo-oophorectomy was performed. Histopathology confirmed moderately-poorly differentiated SLCT. Conclusions The CEUS pattern of SLCT (rapid heterogeneous hyperenhancement with early wash-out) is similar to that of malignant ovarian tumors. The diagnosis of SLCT cannot rely solely on imaging findings. Integrated clinical and laboratory findings are crucial for differentiating SLCT from ovarian cancer.